Randomized controlled trial demonstrates response to a probiotic intervention for metabolic syndrome that may correspond to diet. (31st December 2023) - Wastyk, Hannah C.; Perelman, Dalia; Topf, Madeline; Fragiadakis, Gabriela K.; Robinson, Jennifer L.; Sonnenburg, Justin L.; Gardner, Christopher D.; Sonnenburg, Erica D.
ABSTRACT: An individual's immune and metabolic status is coupled to their microbiome. Probiotics offer a promising, safe route to influence host health, possibly via the microbiome. Here, we report an 18-week, randomized prospective study that explores the effects of a probiotic vs. placebo supplement on 39 adults with elevated parameters of metabolic syndrome. We performed longitudinal sampling of stool and blood to profile the human microbiome and immune system. While we did not see changes in metabolic syndrome markers in response to the probiotic across the entire cohort, there were significant improvements in triglycerides and diastolic blood pressure in a subset of probiotic arm participants. Conversely, the non-responders had increased blood glucose and insulin levels over time. The responders had a distinct microbiome profile at the end of the intervention relative to the non-responders and placebo arm. Importantly, diet was a key differentiating factor between responders and non-responders. Our results show participant-specific effects of a probiotic supplement on improving parameters of metabolic syndrome and suggest that dietary factors may enhance stability and efficacy of the supplement.